Classification of Product Review Sentiment Using Naive Bayes and Support Vector Machine Algorithms - Pandi Barita Nauli Simangunsong; Matias Julyus Fika Sirait; Tuti Andriani (Cattleya Darmaya Fortuna, 2026)
This review synthesizes research on